Pengaruh Debt To Equity Ratio, Long Term Debt To Equity Ratio ,Return On Asset dan Volume Penjualan terhadap Harga Saham pada Industri Rokok yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Josua Fery Anto Pardosi (Universitas Batanghari Jambi, 2021)
The purpose of this study is to analyze the influence of debt to equity ratio (DER), long tern debt to equity ratio (LTDR), return on asset (ROA) and simultaneous and parisal growth rate on stock prices in Industri Rokok Yang Terdaftar di Bursa Efek Indonesia Period 2015-2019. The Data used in this research is the annual financial statements such as the balance sheet and the profit and loss in Industri Rokok Yang Terdaftar di Bursa Efek Indonesia Period 2015-2019. The data source in this research is the official website of the Indonesian Stock exchange. This research used a multiple linear regression analysis tool used to figure out the direction of the relationship between the independen variable of the dependen variabel. Then, to answer the purpose of this research is used the F-test anf t-test and koefisien determinasi. Industri Rokok has a fairly good position in Indonesia, another reason related to the selection of research objects is the Cigarette Industry listed on the Indonesia Stock Exchange occupies the third position of the four manufacturing industries that are in demand by investors, it is because the Cigarette Industry listed on the Indonesia Stock Exchange has good prospects, judging from the basic needs needed by humans. Regression result of Y = 2,131 + 0,237 X1 + 0,034 X2 + 1,287 X3 – 0,174 X4 + e meaning is debt to equity ratio, long term debt equity ratio, return on asset and growth rate against the stock price of 42%. In other words, stock return variables can be explained or influenced by variables debt to equity ratio, long term debt equity ratio, return on asset and growth rate of 42%, while the remaining 58% is explained or influenced by other variables that are not studied. Simultaneously DER, LTDER, ROA, growth rate has a significant effect on the stock price. Partially DER, LTDER and growth rates have no effect on the stock price. Meanwhile, variable ROA has an effect on the stock price